Specificity and the contents of vocational training of the future teacher of music in an orchestral class (Pedagogy of Higher and Secondary Education, 2006)
The article defines the role of the orchestral class in the system of the music teacher's professional training. The specific character and the content of the educational activities of the Art Department students of the Pedagogical I University in the chamber orchestra are covered in it.
Keywords: pedagogical modeling; .drills of the orchestral performing; educational activity; erforming practice; system of methods of the work with the children's orchestra (a string ensemble); pedagogical repertoire